2022
DOI: 10.1007/s10741-022-10268-0
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 21 in heart failure

Abstract: Fibroblast growth factor 21 (FGF21) is a peptide hormone involved in energy homeostasis that protects against the development of obesity and diabetes in animal models. Its level is elevated in atherosclerotic cardiovascular diseases (CVD) in humans. However, little is known about the role of FGF21 in heart failure (HF). HF is a major global health problem with a prevalence that is predicted to rise, especially in ageing populations. Despite improved therapies, mortality due to HF remains high, and given its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 114 publications
0
8
0
5
Order By: Relevance
“…Tucker et al [ 19 ] concluded in their review study, which summarized preclinical and clinical evidence, that FGF21 plays a function in HF. Preclinical studies have demonstrated that FGF21 has a role in the development of heart failure by mitigating oxidative stress, cardiac hypertrophy, and inflammation in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Tucker et al [ 19 ] concluded in their review study, which summarized preclinical and clinical evidence, that FGF21 plays a function in HF. Preclinical studies have demonstrated that FGF21 has a role in the development of heart failure by mitigating oxidative stress, cardiac hypertrophy, and inflammation in cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“… 41 FGF‐21 has also been implicated in the pathogenesis of HF through the modulation of oxidative stress. 42 Tucker et al 43 reported that FGF‐21 is involved in the pathophysiology of HF by preventing oxidative stress, cardiac hypertrophy, and inflammation in cardiomyocytes and that its level is elevated in patients with HF, suggesting that FGF‐21 may be used as a biomarker for the prediction and diagnosis of HF. Another study found that the serum FGF21 levels were elevated in hospitalized patients with ST‐segment elevation myocardial infarction (STEMI), confirming that elevated serum FGF‐21 level may be a strong predictor of HF during hospitalization in patients with STEMI.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of in ammation extends to FGF-mediated cell survival pathways, as in ammatory signals may modulate these pathways, potentially compromising the anti-apoptotic effects of FGF and in uencing overall cardiomyocyte survival. FGF signaling's involvement in angiogenesis and its promotion of cardiomyocyte proliferation during development may be negatively affected by in ammation, potentially leading to impaired vascularization and a reduction in the expansion of the cardiomyocyte population [140,141]. The intricate crosstalk between FGF signaling and other pathways, such as Wnt and Notch, is also susceptible to disruption by in ammation, potentially compromising the integrated signaling network that regulates cardiac cell fate.…”
Section: Fgf Signaling Pathwaymentioning
confidence: 99%